Selections from vocal works published by Schott - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Germany; B. Schott Söhne; Mainz)
Includes the songs "Das Glück der Freundschaft," op. 88, and "La partenza," WoO 124, with text in German and Italian for both.